The Relationship Between Resilience and Entrepreneurial Attitude of University Students in Semarang - Marliyah, Lili (Indonesian Journal of Business and Entrepreneurship, 2023)
A student's life skills to be an entrepreneur are challenging when starting a new business. It takes resilience to adapt and an attitude of responding to difficulties for education graduates to have additional entrepreneurial competencies. The life skills needed follow the vision of Ivet Semarang University, namely technopreneurship university. This research aimed to determine the relationship between resilience and students' entrepreneurial attitudes. This study uses a quantitative approach with ex post facto research methods. Sampling was carried out incidentally using a simple linear regression analysis method. The results show that (1) the resilience level of students can develop a positive adaptive attitude that allows them to be entrepreneurs because there is a positive relationship, (2) the results from the individual dimension, indicator from the highest percentage of individual personal skills shows the high category 19%, (3) results from the indicator with the highest future-oriented percentage of 19%, (4) based on the significance value (2 tailed) output in table 0.000 <0.05 means that there is a significant relationship between resilience and entrepreneurial attitude. The implication is important for individuals with high resilience abilities to become solid individuals and role models and have resilience in dealing with problems in entrepreneurship. Keywords: resilience, entrepreneurial attitude, students, relationships, ex post facto research